PENYULUHAN PERAN DIGITAL MARKETING DALAM MENINGKATKAN PENJUALAN PRODUK UMKM KERIPIK CIPING DESA SUKAWANA CURUG KOTA SERANG - Reni Febriani (ABDIKARYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2021)
This community service basically purpose to provide training and mentoring to “UMKM Keripik Ciping” in Sukawana Village so that they can innovate on the “Keripik Ciping” marketing system which is still traditional and has low mastery of information technology in marketing. Based on these problems, if business actors need knowledge about business management and product commercialization concepts, especially those related to packaging design and marketing using information technology. The method of implementing community service activities is in the form of counseling/socialization on improving packaging design, marketing, training and assisting in the digitalization process of marketing/digital marketing through marketplace/social media. Through this activity, business actors are expected to be able to manage their business for the better and be able to expand market share so that they can support business development and progress which in turn can increase income for “UMKM Keripik Ciping” business actors.